The Elements of Setting in The Novel Sukreni Gadis Bali By A.A. Pandji Tisna - M. Afan (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
This library research aimed at finding out The Elements of Setting in the Novel Sukreni Gadis Bali By A.A.Pandji Tisna. In analyzing a literary work, we have to be able to give a consideration to analyze the elements in a literary work as a work of art, such as form, content, value, and society, which designed a literary work. Setting is everything that happens somewhere at some time. It is the element of fiction which reveal to the reader the where and when of the events occurred, we call setting. It refers to the point in time and space at which the events of the plot occur that can be classified into two types of setting, Neutral setting and the spiritual setting. In relation to those main discussion, this research used qualitative descriptive designed. The Novel entitled Sukreni Gadis Bali is a main source data, while other books reference are the secondary resource to support not only data collection but also data analysis procedure. After doing all the research procedure, it is found out that there are four elements of setting in the Novel Sukreni Gadis bali by AA.Panji Kusna. They are (1) the actual geographical location, including topography, scenery, even the details of room’s interior;(2) the occupation of modes of day-to-day existence of the characters;(3) the time in which the action takes place, e.g., historical period, season of the year; (4) the religious, moral, intellectual, social, and emotional environment of the characters.